Symphysis Pubis Osteomyelitis: An Uncommon Complication after Robotic Assisted Radical Prostatectomy—Case Description with Literature Review - Jad A. Degheili; Mazen M. Mansour; Rami W. Nasr (Case Reports in Urology)
Prostate cancer is the most common solid cancer among American men. Although there are various modalities for treatment, including radical prostatectomy among many others, the former is, nevertheless, not without any accompanied complications. Other than the well-known surgical complications such as erectile dysfunction, urinary incontinence, and voiding dysfunction, osteomyelitis of the symphysis pubis is not a well-understood complication, with various hypotheses explaining its pathogenesis. Although osteomyelitis of the pubis symphysis has been reported after endoscopic urological procedures such as transurethral resection of the prostate, it has rarely been reported after robotic surgeries. We hereby report, to the best of our knowledge, the first osteomyelitis of the pubis symphysis, after robotic prostatectomy, in a patient with prostate cancer and no previous radiation therapy.